The effects of aluminum concentration on the microstructural and electrochemical properties of lithium lanthanum zirconium oxide. Issue 41 (28th September 2022) - Moy, Alexandra C.; Häuschen, Grit; Fattakhova-Rohlfing, Dina; Wolfenstine, Jeffrey B.; Finsterbusch, Martin; Sakamoto, Jeff
Abstract : LLZO is a promising solid-state electrolyte for Li-metal batteries. It is known that Al stabilizes the high conductivity cubic phase. In this study, the effect of Al concentration on the microstructure and electrochemical behavior was investigated. Abstract : Cubic lithium lanthanum zirconium oxide (Li7− x Al x La3 Zr2 O12, LLZO) garnet has gained attention as a promising next-generation electrolyte for lithium batteries due to its high ionic conductivity and chemical stability with lithium metal. The high conductivity can be achieved through doping over a range of aluminum concentrations. In this study, we hot-pressed samples to achieve <2% nominal porosity with aluminum concentrations from x = 0.25–0.55 mol to understand the effect of aluminum on microstructure and electrochemistry. It was observed that beyond the aluminum solubility limit ( x = ∼0.40), resistive secondary phases formed at the grain boundaries. As a result, the percent grain boundary resistance increased from 17.6 to 41.2% for x = 0.25 and x = 0.55, respectively. Both the grain boundary and bulk activation energies remained relatively constant as the aluminum concentrations increased (∼0.44 eV and ∼0.39 eV, respectively). It was, therefore, surmised that the mobility term of the Nernst–Einstein equation was roughly independent of aluminum concentration and the major variable controlling bulk conductivity was the number of lithium charge carriers. As a result, as the aluminum concentration increased from x = 0.25 to x = 0.55 the bulk conductivity decreased from 0.56 to 0.15 mS cm −1 . Following these trends of increasing grain boundary resistance and decreasing bulk conductivity with increasing aluminum concentration, x = 0.25 had the highest total conductivity (0.46 mS cm −1 ). We demonstrated that aluminum concentration has a significant effect on the microstructure and electrochemical properties of LLZO. We believe this work could help understand how to link processing, microstructure, and electrochemical properties to guide the manufacturing of LLZO for use in solid-state batteries.